2021
DOI: 10.1038/s41438-021-00610-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, phenological, and transcriptional analyses provide insight into the diverse flowering traits of a mutant of the relic woody plant Liriodendron chinense

Abstract: Flowering is crucial to plant reproduction and controlled by multiple factors. However, the mechanisms underlying the regulation of flowering in perennial plants are still largely unknown. Here, we first report a super long blooming 1 (slb1) mutant of the relict tree Liriodendron chinense possessing a prolonged blooming period of more than 5 months, in contrast to the 1 month blooming period in the wild type (WT). Phenotypic characterization showed that earlier maturation of lateral shoots was caused by accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Moreover, our study identified more TFs than previously reported, suggesting the role of a more complex transcriptional regulation network for mutant plant development (Yang et al, 2018). Particularly, the expression levels of genes from the same TF families varied in different samples, which was consistent with a previously reported study on flowering traits of Liriodendron chinense mutant (Sheng et al, 2021). These results suggest that compared with wild-type plants, some DEGs encoding transcription factor may play a role in mutant development and affect the generation of specific traits, leading to differential traits between wild-type and mutant plants.…”
Section: Changes In Tfs In the Mutant Plantssupporting
confidence: 91%
“…Moreover, our study identified more TFs than previously reported, suggesting the role of a more complex transcriptional regulation network for mutant plant development (Yang et al, 2018). Particularly, the expression levels of genes from the same TF families varied in different samples, which was consistent with a previously reported study on flowering traits of Liriodendron chinense mutant (Sheng et al, 2021). These results suggest that compared with wild-type plants, some DEGs encoding transcription factor may play a role in mutant development and affect the generation of specific traits, leading to differential traits between wild-type and mutant plants.…”
Section: Changes In Tfs In the Mutant Plantssupporting
confidence: 91%
“…Using A. thaliana SnRK2s as a reference, the protein sequences of the L. chinense SnRK2 family members were found in a specific genome database ( , accessed on 5 June 2022). SnRK2’s protein sequence was analyzed by the Pfam database ( , accessed on 5 June 2022) and matched with a domain profile (PF00069) [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…tulipifera , also known as the tulip tree or yellow poplar, is a particular species found in the eastern United States that may grow to heights of up to 30.48 m [ 1 ]. Liriodendron is an excellent decorative tree for landscaping because of its straight trunk, conical crown, unusual leaf shape, and tulip-shaped blooms [ 2 , 3 ]. Liriodendron has also been frequently planted as an industrial timber species because of its quick growth and adaptable wood with superior working characteristics [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations